Maternal Liver and Egg Thiamine Concentrations in Walleye from Lake Oahe, South Dakota - Rosburg, Alex; Voorhees, Jill; Barnes, Michael E. (European Journal of Applied Sciences, 2022)
Thiamine, vitamin B1, cannot be synthesized by fish. Therefore, developing embryos are reliant on thiamine stores deposited during oogenesis. Thiaminase, which breaks down thiamine in predatory fish, has been suggested as the probable reason for the poor reproductive success in salmonids. Similarly, walleye Sander vitreus reproduction may also be hampered by thiaminase-containing diets. This study documented maternal liver and egg thiamine concentrations of walleye populations from the Cheyenne, Moreau, and Grand rivers of Lake Oahe, South Dakota, USA in 2000, 2001, 2002, and 2004. Thiamine concentrations were generally lowest in the eggs from the Cheyenne River. Free thiamine, thiamine monophosphate, and total thiamine were all significantly lower in eggs from the Cheyenne River compared to the Moreau and Grand Rivers. Maternal liver thiamine pyrophosphate and total thiamine followed a similar pattern. Egg survival to hatch varied significantly between locations, at 30.5%, 41.4%, and 56.8% in the Cheyenne, Moreau, and Grand Rivers, respectively, but was not significantly correlated with any form of egg thiamine. Considerable year-to-year variation was observed when data from the locations were pooled; egg free thiamine, thiamine monophosphate, and total thiamine were significantly higher in 2002. The lowest mean egg total thiamine level of 2.6 nmol/g was recorded in 2000. Liver free thiamine and thiamine monophosphate were weakly, but significantly negatively correlated with egg survival to hatch to hatch. Egg survival to hatch was significantly negatively correlated with maternal length. The results were likely impacted by the unexpected catastrophic loss of walleye forage because of flooding in 2003.